Evaluation of empathy in Argentina child population - Richaud de Minzi, María Cristina (2008)
It was observed that empathy predicts prosocial behaviour in children and that empathic people are less aggressive due to their emotional sensitivity and capacity to understand the potential negative consequences for themselves and others that can arise from aggression. For this reason, empathy appears negatively related to aggression and positively related to prosocial behaviour. Empathy includes cognitive processes and affective experiences, and it means at the same time a predominantly cognitive answer of understanding about other person feelings and an emotional communion. Davis (1983) defines empathy as a multidimensional construct. His scale includes cognitive components: Perspective Taking and Fantasy, and emotional components: Empathic Concern and Personal Distress. We will present the Argentine adaptation of The Interpersonal Reactivity Index (IRI) of Davis (1980) that has 28 items, with a Likert answer format, with five options, counts from 0 to 4. The IRI Spanish version (Mestre, Frias, & Samper, 2004) was administered to two independent samples (N= 633 y 652,) of Argentine children, both sexes, 9 to 12 years of age, that attended to primary schools of Buenos Aires city. Although Davis’ IRI keeps, in Argentine samples, the same basic structure indicating that theoretical model is preserved, it presents for Argentine children meaning differences in some of the items. Mainly, it would be interesting to explore deeper the hypothesis about an emotional intelligence process more than a rational perspective taking. With respect to the remaining differences, they are generally due to different cultural manner in items interpretation, and probably to age influence.